Microbiological Analysis of Primary Molars Restored with Stainless Steel Crowns Compared to Healthy Molars - Andrea Rubio; Tanya Pereira; Juan Ramón Boj; Teresa Vinuesa (Microorganisms)
One of the best restorative treatment options for large carious lesions is the placement of stainless-steel crowns (SSC), but there are few studies evaluating if there is any change in the microbiota in teeth restored with SSCs. In order to asses if any difference exists, 33 children between 4 and 10 years were studied. One primary molar restored with an SSC as well as one healthy primary molar were selected from each child. Subgingival plaque was collected with a curette and cultured on horse blood agar (Columbia) and selective and nonselective media. A quantitative analysis was performed by means of the counting of the colony-forming units per milliliter (cfu/mL) grown in the nonselective media and compared with the bacterial load measured by means of a 16S qPCR with bacterial universal primers. A descriptive statistical analysis was performed to evaluate the results. No significant differences were observed in the total 16S qPCR according to sample type. Streptococci were observed in all the studied children. Porphyromonas gingivalis was observed in 18% of patients and Prevotella intermedia in 42%. Campylobacter was observed in 81% and Neisseria in 88%. C. albicans was observed in only one patient. No significant differences were found between both groups. Part of the child population studied had anaerobic bacteria. There is no clear association between the presence of periodontopathogens and SSC.